Are Inflows of FDI Good for Russian Exporters? - Poupakis, Stavros (World Bank, Washington, DC, 2020)
This study examines whether foreign direct investment inflows facilitate upgrading of export quality in host countries. The analysis focuses on the Russian Federation and uses customs data merged with firm-level information from Orbis. The results show a positive relationship between the quality of products exported by domestic firms and the presence of foreign affiliates in the upstream (input-supplying) industries. This relationship is present irrespective of export destination or foreign direct investment origin. The results are robust to using different proxies to measure product quality.